Calcific uremic arteriolopathy (CUA) among Malaysian dialysis patients: clinical characteristics, treatment, and outcome - Lee, Yee Wan; Tan, Min Hui; Bavanandan, Sunita; Bee, Boon Cheak; Lim, Christopher Thiam Seong; Mohd, Rozita; Liew, Yew Foong; Loh, Chek Loong; Liu, Wen Jiun; Mohamad Nor, Fariz Safhan; Harun, Zaiha; Rahmat, Korina; et al. (Macrothink Institute, 2024)
Background: Calcific uremic arteriolopathy (CUA) is a rare but debilitating disease affecting patients with kidney disease. Reported risk factors of CUA in the literature include female sex, obesity, diabetes mellitus, and vitamin K antagonists' (VKAs) usage. CUA prevalence in Malaysia is unknown and has not been reported before. Methods: A multicenter observational study was conducted in 13 centers all over Malaysia to study the clinical characteristics, treatment, and outcomes of CUA. The data of patients confirmed with CUA between January 1, 2016, and December 31, 2021, was collected from medical records by each center’s nephrologists. Results: Out of 33 confirmed CUA cases, 69.7% were females, and 66.7% were Malay with a mean age of 47.33 ± 13.80 years old. The mean BMI was 25.66 ± 9.77 kg/m2, and 18.2% were classified as obese (BMI > 30). Two-thirds of the patients were on hemodialysis (HD), and the mean dialysis vintage was 6.2 ± 4.11 years. A majority (87.9%) have hypertension, 33.3% are diabetic, and 27.3% have coronary artery disease. Only 15.2% of the patients were on warfarin at the time of diagnosis. A total of 78.8% of patients were taking calcium-based phosphate binders during diagnosis. Investigation results showed calcium, 2.44 ± 0.29 mmol/L; phosphate, 2.18 ± 0.67 mmol/L; CaXPO4 = 5.41 ± 1.90; and parathyroid hormone, 181.14 ± 153.23 pmol/L. About half (54.5%) had skin biopsy confirmation done. Distribution of lesions was 57.6% peripheral and 30.3% central. For treatment of CUA, there were 57.6% usage of non-calcium-based phosphate binders, 48.5% cinacalcet, 30.3% sodium thiosulphate, and 33.3% had parathyroidectomy. Half (54.5%) of our CUA patients died within three months from diagnosis. The mean time from diagnosis to mortality was 4.12 ± 5.59 months. A majority (45.5%) died from septicemia caused by infections. Interestingly, there were a few rare presentations of CUA such as pulmonary calciphylaxis, heart and lung calcifications, liver and spleen calcifications, and genital lesions. One patient had resistant CUA and was given a trial of lipid apheresis for 10 sessions. Conclusion: This is the first and largest multicenter study looking into the characteristics, treatment, and outcome of CUA in Malaysia. Majority of patients in Malaysia undergo HD as kidney replacement therapy; hence, our results correlate with this. The incidence of CUA was estimated to be 6.6 per 10,000 dialysis patients in this study and the mortality rate is very high. This is consistent with worldwide data which reported mortality as high as 60%.